The Politics of Children’s Rights and Representation - Sandin, Bengt; Josefsson, Jonathan; Hanson, Karl; Balagopalan, Sarada (Studies in Childhood and Youth, 2023)
XVI, 337 p. 7 illus., 5 illus. in color.